Patient Satisfaction, Doctor Effort, And Interview Location : Evidence From Paraguay - Das, Jishnu (The World Bank, 2006)
To examine the relationship between patient satisfaction and doctor performance, the authors observed 2,271 interactions between 292 doctors and their patients in 98 clinics and hospitals in Paraguay and conducted an exit-survey with the same patients as they left the clinic. For a subsample of 64 facilities they also interviewed patients who visited the facility within the last week. There are three patterns in the data: (1) Patient satisfaction is positively correlated with doctor effort, measured as a combination of time spent, questions asked, and examinations performed after controlling for observed doctor and patient characteristics; (2) However, accounting for unobserved doctor characteristics dramatically reduces the level of significance and size of correlation between effort and satisfaction, showing that much of the positive relationship is driven by these unobserved doctor-specific factors; and (3) Reported satisfaction is significantly lower for patients interviewed at home compared with those interviewed at the clinic. This leads the authors to conclude that even if patient satisfaction reflects some aspects of the doctor's performance, unobserved heterogeneity combined with survey biases limit the widespread applicability of patient satisfaction as an indicator of doctor performance